2021
DOI: 10.1177/00031348211060414
|View full text |Cite
|
Sign up to set email alerts
|

General Surgery Twitter during COVID-19: Tweets, Trends, and Implications for Recruitment Strategies

Abstract: Background The COVID-19 pandemic has disrupted traditional resident recruitment practices, requiring virtual interviews and new forms of outreach. Social media, such as Twitter, is one tool programs can use to connect with applicants. This study sought to assess changes in Twitter use during the COVID-19 pandemic among general surgery programs. Methods Twitter and residency program websites were queried for public Twitter accounts related to general surgery residency programs. Publicly available tweets for ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Czawlytko et al [ 18 ] demonstrated that 71% of prospective radiology residents viewed a program’s social media account to learn about the program, without specifying the specific platform. Although Instagram was the most frequently used tool in our effort, Cox et al [ 19 ] have demonstrated significant expansion in general surgery programs’ Twitter use since the start of the pandemic. Similarly, emergency medicine residency programs increased social media use by 34% in 2020, and the authors felt the emphasis on web-based platforms in the setting of the pandemic was a significant catalyst [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Czawlytko et al [ 18 ] demonstrated that 71% of prospective radiology residents viewed a program’s social media account to learn about the program, without specifying the specific platform. Although Instagram was the most frequently used tool in our effort, Cox et al [ 19 ] have demonstrated significant expansion in general surgery programs’ Twitter use since the start of the pandemic. Similarly, emergency medicine residency programs increased social media use by 34% in 2020, and the authors felt the emphasis on web-based platforms in the setting of the pandemic was a significant catalyst [ 20 ].…”
Section: Discussionmentioning
confidence: 99%